Assessment of Surface Water Quality Using Malaysia Water Quality Index (MWQI) And National Sanitation Foundation Water Quality Index (NSFWQI) During Road Construction Activities - NURAMANINA,; Khamidun, Mohd Hairul (Recent Trends in Civil Engineering and Built Environment, 2021)
Water quality explains the condition of the water, include the characteristics of chemical, physical, and biological. The study of this project is basically on the surface water quality assessment by using Malaysian WQI and NSFWQI based on secondary data of monitoring the water quality in road construction activities. Malaysia WQI use six parameters which are biochemical oxygen demand (BOD), chemical oxygen demand (COD), dissolved oxygen (DO), NH3N, pH, and total suspended solids (TSS) to evaluate the water quality index while NSFWQI only use five parameters which are biochemical oxygen demand (BOD), total suspended solids (TSS), turbidity, pH and dissolved oxygen (DO). By assessing these water quality index, level of water quality can be identified and classifying into few classes based on their condition. Based on calculation of water quality index using Malaysia WQI and NSFWQI, the index value for these two indexes are different because the difference number of parameters used and the most accurate index of water quality is Malaysia WQI. The study significance is to determine level of surface water quality at road construction activities.